Предмет: Математика,
автор: kotikalsu
решите пожалуйста
6 5/8-(3 3/8+1 7/8)=
(8-4 3/11)+2 8/11=
11 1/7-(5 4/7+3 6/7)=
Ответы
Автор ответа:
1
Ответ:
Пошаговое объяснение:
6 5/8-(3 3/8+1 7/8)= 6 5/8 - 4 10/8 = 6 5/8 - 5 2/8 = 1 3/8
(8-4 3/11)+2 8/11= 3 8/11 + 2 8/11 = 5 16/11 = 6 5/11
11 1/7-(5 4/7+3 6/7)= 11 1/7 - 8 10/7 = 11 1/7 - 9 3/7 = 1 5/7
Похожие вопросы
Предмет: Литература,
автор: sofiasavka043
Предмет: Математика,
автор: kseniadovgolenko
Предмет: Английский язык,
автор: dgleb2329
Предмет: Алгебра,
автор: Dimbo22
Предмет: Математика,
автор: mirodjip